Reestablishment of Hymenaea travassii (Leguminosae, Caesalpinioideae), a species endemic to the Bolivian Chaco - Pinto, Rafael Barbosa; Mansano, Vidal De Freitas; Tozzi, Ana Maria Goulart De Azevedo (Phytotaxa, 2015)
In Lee & Langenheim’s taxonomic revision of the genus Hymenaea (Leguminosae, Caesalpinioideae), the species Hymenaea travassii was considered a species of dubious status. A detailed analysis of the type material and additional specimens, clearly indicates, however, that this is a distinct species, endemic to the Bolivian “chaco”. The species can be distinguished by a combination of its habit, the texture of the bark and the shape and size of its leaflets. This study proposes the reestablishment of Hymenaea travassii as a distinct species, based on morphology. A species description, a key to distinguish Hymenaea travassii from related species, and a summary of its geographical distribution are presented, together with an illustration.